Pola Komunikasi Pustakawan Kepada Pemustaka ‘Rohiqol Ilmi’ - Farhan Farhan; Novian Ramadhan Dwiharta; Faidatul Jannah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research aims to describe the communication patterns of librarians to users of the 'Rohiqul Ilmi' Library, Binor Village, Paiton District, Probolinggo Regency. Library staff must carry out library management and services optimally so that the library becomes a place that is more appreciated by users. Each librarian has different communication patterns according to their characteristics and personality traits. What is the librarian's communication pattern like in serving users of the 'Rohiqul Ilmi' village library in Binor village, Paiton, Probolinggo? This research is qualitative research with a case study approach. Data collection was carried out through observation, interviews and documentation, between August and October 2023, all data collected from observation, interviews and documentation was analyzed descriptively within the interdisciplinary communication science paradigm. The results of the research state two important things, namely: (1) the communication patterns of Rohiqul Ilmi' village library librarians tend to be passive and less interactive. They tend to accept and implement activities proposed or mandated by policy makers to be implemented in village libraries, such as great parent activities, implementation of KKN and others; (2) assertive communication patterns are also the choice of librarians in serving users of the 'Rohiqul Ilmi village library. When librarians convey their opinions or ideas, they do not appear to offend other people or partners, either verbally or non-verbally, such as with a smile and thumbs up to show silent agreement.